'No sovereign nation, no reservation': producing the new colonialism in Cayuga Count(r)y. Issue 1 (2nd January 2018) - Wolkin, Kenneth; Nevins, Joseph
ABSTRACT: 'No sovereign nation, no reservation': producing the new colonialism in Cayuga Count(r)y. Territory, Politics, Governance . Since 1980, the Cayuga Nation has worked through various US politico-legal mechanisms to establish sovereignty over land taken from them by European settlers and their descendants in what is today New York State beginning in the 1700s. When, in 2005, the US Supreme Court refused to review a lower court's dismissal of their case, the Cayugas began purchasing land they claim from local (non-Cayuga) property owners. Relatedly, they petitioned the US Bureau of Indian Affairs to place the land that they collectively own into federal trust, which would exempt them from various taxes. These efforts have engendered strong opposition from elements of the non-Native population, particularly the organization Upstate Citizens for Equality (UCE). This article interrogates the discourse of UCE, and its allies and antecedents, one that effectively nationalizes the Cayugas by producing them as 'normal' US citizens, as well as that of the federal courts. It illustrates how a discourse emphasizing equality, fairness, (US) nationhood and private property obfuscates the Cayuga's dispossession and the nature of their land claim, to reproduce a colonized space, and to give rise to what we call 'the new colonialism', producing an impasse whose overcoming requires a far-reaching rethinking of territory and sovereignty.